2018
DOI: 10.1074/jbc.ra118.003298
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6–mediated trans-signaling inhibits transforming growth factor-β signaling in trabecular meshwork cells

Abstract: Glaucoma is one of the major causes of blindness, and transforming growth factor-β2 (TGF-β2) has been found to be elevated in the aqueous humor of eyes with primary open-angle glaucoma (POAG). TGF-β2 in aqueous humor causes the glaucoma-related fibrosis of human trabecular meshwork (HTM), suggesting an important role of TGF-β in POAG pathogenesis. Here, we sought to elucidate the effects of IL-6 trans-signaling on TGF-β signaling in HTM cells. Using a multiplex immunoassay, POAG patients decreased IL-6 levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 37 publications
1
24
0
1
Order By: Relevance
“…This is possibly due to secondary glaucoma being caused by underlying diseases that are associated with a high IL-6 level, including PEX syndrome, intraocular inflammation, DR, ROP and RD 248 . And in regard to the lack of IL-6 increase in primary glaucoma, it is interesting to note previous reports showing that soluble IL-6 receptor (sIL-6R) but not IL-6 is elevated in the aqueous humour of POAG 49 . This interaction between IL-6 and sIL6R is known to exhibit the inhibitory action of TGF-β-induced up-regulation of fibrotic changes in vitro 49 , suggesting that trans-signalling of IL-6 could be a potential target of POAG treatment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is possibly due to secondary glaucoma being caused by underlying diseases that are associated with a high IL-6 level, including PEX syndrome, intraocular inflammation, DR, ROP and RD 248 . And in regard to the lack of IL-6 increase in primary glaucoma, it is interesting to note previous reports showing that soluble IL-6 receptor (sIL-6R) but not IL-6 is elevated in the aqueous humour of POAG 49 . This interaction between IL-6 and sIL6R is known to exhibit the inhibitory action of TGF-β-induced up-regulation of fibrotic changes in vitro 49 , suggesting that trans-signalling of IL-6 could be a potential target of POAG treatment.…”
Section: Discussionmentioning
confidence: 98%
“…And in regard to the lack of IL-6 increase in primary glaucoma, it is interesting to note previous reports showing that soluble IL-6 receptor (sIL-6R) but not IL-6 is elevated in the aqueous humour of POAG 49 . This interaction between IL-6 and sIL6R is known to exhibit the inhibitory action of TGF-β-induced up-regulation of fibrotic changes in vitro 49 , suggesting that trans-signalling of IL-6 could be a potential target of POAG treatment. Despite the fact that IL-6 may not directly contribute to OAG pathogenesis, studies confirmed an elevated level of TNFα and IL-8 in the OAG eye 249 , 250 , which emphasizes that the inflammatory process is involved in the OAG progression.…”
Section: Discussionmentioning
confidence: 98%
“…Interleukin-6 (IL-6) is a phosphorylated glycoprotein containing 185 amino acids. IL-6 is one of the most widely recognized cytokines associated with inflammation [ 11 , 12 ]. It regulates several important cellular pathways including: cell proliferation, differentiation, immune responses, invasion, metastasis as well as carcinogenesis [ 13–16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we can speculate that, in our experimental conditions, TGF-β exerts a role as a key regulator of the cell-matrix interactions [62]. In our platform, chronic activation of IL6, due to oxidative stress, did not repress the TGF-signaling [53] but, on the contrary, its effect resulted in an increase in outflow resistance with a 3D-HTMC-contractility alteration [61].…”
Section: Discussionmentioning
confidence: 64%
“…In our 3D-Model, the exposure of TM cells to only oxidative stress led to an increase in pro-inflammatory and pro-fibrotic cytokines and MMP gene expression [51][52][53][54] (Figure 4A-C).…”
Section: Discussionmentioning
confidence: 88%